Diabetic complications and prospective immunotherapy - Reynolds, Lewis; Luo, Zhengkang; Singh, Kailash (Frontiers in Immunology, 2023)
The incidence of Diabetes Mellitus is increasing globally. Individuals who have been burdened with diabetes for many years often develop complications as a result of hyperglycemia. More and more research is being conducted highlighting inflammation as an important factor in disease progression. In all kinds of diabetes, hyperglycemia leads to activation of alternative glucose metabolic pathways, resulting in problematic by-products including reactive oxygen species and advanced glycation end products. This review takes a look into the pathogenesis of three specific diabetic complications; retinopathy, nephropathy and neuropathy as well as their current treatment options. By considering recent research papers investigating the effects of immunotherapy on relevant conditions in animal models, multiple strategies are suggested for future treatment and prevention of diabetic complications with an emphasis on molecular targets associated with the inflammation.